The many uses of mobiles - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2009)
Over the years, ICT Update has covered the many ways in which mobile phones are used to promote agricultural and rural development. The technology has proven so useful that it is likely to remain a popular method of information delivery for some time to come.